CYP3A4 isoenzyme phenotyping for personalisation of pharmacotherapy - E. A. Egorenkov; V. V. Smirnov; V. N. Kuzina; S. P. Dementiev; G. V. Ramenskaya (Регуляторные исследования и экспертиза лекарственных средств, 2018)
The article reviews existing methods of determining CYP3A4 isoenzyme activity. The authors assess the significance of CYP3A4 activity determination and the applicability of these methods in clinical practice to adjust drugs doses and minimize risks of adverse reactions. The article demonstrates the possibility of developing a method for simultaneous determination of several CYP3A4 substrates which is necessary to rule out potential errors arising upon introduction of other P450 cytochrome enzymes into metabolism of some endogenous substrate. It is suggested that blood should no longer be used as a biological object in the study in order to decrease the method’s invasiveness.